Decreased Taurine and Creatine in the Thalamus May Relate to Behavioral Impairments in Ethanol-Fed Mice: A Pilot Study of Proton Magnetic Resonance Spectroscopy - Su Xu PhD; Wenjun Zhu MS; Yamin Wan MD, PhD; JiaBei Wang PhD; Xi Chen PhD; Liya Pi PhD; Mary Kay Lobo PhD; Bin Ren PhD; Zhekang Ying PhD; Michael Morris MD; Qi Cao MD, PhD (Molecular Imaging)
Minimal hepatic encephalopathy (MHE) is highly prevalent, observed in up to 80% of patients with liver dysfunction. Minimal hepatic encephalopathy is defined as hepatic encephalopathy with cognitive deficits and no grossly evident neurologic abnormalities. Clinical management may be delayed due to the lack of in vivo quantitative methods needed to reveal changes in brain neurobiochemical biomarkers. To gain insight into the development of alcoholic liver disease–induced neurological dysfunction (NDF), a mouse model of late-stage alcoholic liver fibrosis (LALF) was used to investigate changes in neurochemical levels in the thalamus and hippocampus that relate to behavioral changes. Proton magnetic resonance spectroscopy of the brain and behavioral testing were performed to determine neurochemical alterations and their relationships to behavioral changes in LALF. Glutamine levels were higher in both the thalamus and hippocampus of alcohol-treated mice than in controls. Thalamic levels of taurine and creatine were significantly diminished and strongly correlated with alcohol-induced behavioral changes. Chronic long-term alcohol consumption gives rise to advanced liver fibrosis, neurochemical changes in the nuclei, and behavioral changes which may be linked to NDF. Magnetic resonance spectroscopy represents a sensitive and noninvasive measurement of pathological alterations in the brain, which may provide insight into the pathogenesis underlying the development of MHE.